Effect of apomorphine on growth hormone and prolactin secretion in schizophrenic patients, with or without oral dyskinesia, withdrawn from chronic neuroleptic therapy. Issue 9 (September 1976) - Ettigi, P; Nair, N P; Lal, S; Cervantes, P; Guyda, H
Abstract : Serum growth hormone (GH) and prolactin (PRL) concentrations were measured after administration of the dopamine receptor agonist, apomorphine HC1 (0.75 mg subcutaneously), to 17 chronic schizophrenic patients, four of whom had an oral dyskinesia, who were withdrawn from chronic neuroleptic therapy for periods of two to 15 weeks, and in 21 control subjects (normal volunteers or physically healthy alcoholics not exposed to neuroleptics). Six of the schizophrenic patients, but none of the controls, had raised baseline levels of GH (greater than 6 ng/ml). After apomorphine all controls showed an increase in serum GH with a peak concentration of 9 ng/ml or more, whereas eight subjects withdrawn from neuroleptics showed an inadequate response (peak less than 6 ng/ml) and in two others an inadequate response was obtained on one of two trials. The peak GH concentration was significantly less after apomorphine in patients withdrawn from neuroleptics (11.90 +/- 3.19 ng/ml) compared with controls (20.80 +/- 2.11 ng/ml) (P less than 0.05). Among patients withdrawn from neuroleptics, those with an oral dyskinesia had significantly lower peak GH concentration 2.46 +/- 0.93 ng/ml) after apomorphine compared with those without (14.85 +/- 3.83 ng/ml) (P less than 0.05). There were no differences in serum PRL concentrations, before or after apomorphine administration, between patients withdrawn from neuroleptics and controls. In uncontrolled observations none of the four patients with an oral dyskinesia showed any worsening of the movement disorder after apomorphine. These data provide no evidence for supersensitivity of dopamine receptors in chronic schizophrenic patients withdrawn from chronic neuroleptic therapy.